Learning Race and Ethnicity: Youth and Digital Media - Everett, Anna (The John D. and Catherine T. MacArthur foundation series on digital media and learning, 2008)
An exploration of how issues of race and ethnicity play out in a digital media landscape that includes MySpace, post-9/11 politics, MMOGs, Internet music distribution, and the digital divide.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé